A Case Study on the Impacts of Social Contexts on a Chinese English as a Foreign Language Learner’s L1 and L2 Identities Development - Xiao, Yuehai; Zhao, Angel (Frontiers in Psychology, 2022)
Informed by the poststructuralist theory, this study investigates the case of Ming, a Chinese professor of English, about the impacts of his first language (L1) and second language (L2) learning experiences, and the changes of social contexts on his L1 and L2 identities construction. It was found that as an English as a Foreign Language (EFL) learner, Ming’s identities development aligned with the poststructuralist theory, in which it is considered dynamic, fluid and conflicting. Ming negotiated and renegotiated his identities in various social contexts in China and the US and finally gained acceptance into the L2 academic community. This study not only analyzes Ming’s experiences with his language learning and identities, but also unravels that conflicts may be part of the process of identities construction, and encourages learners to be persistent and emotionally resilient, while using certain strategies to retain a stable L1 identity so that they can navigate through the negative encounters during the second language acquisition (SLA) process to sustain the development of their identities and L2 abilities.